Sikap Penumpang Garuda Indonesia Terhadap Tray-Set Green Product - Ghita Yasaningthias (Majalah Ilmiah Bijak, 2018)
The purpose of this study was to analyze the relationship between the attitude toward the behavior (ATB) of using the tray set green product to the intention of using the tray-set green product, to analyze the relationship between the subjective norms (SN) to the intention of using the tray-set green product, to analyze the relationship between the perceived behavioral control (PBC) to the intention of using the tray-set green product, to analyze the consumers’ attitudes toward the preferences of the desired attributes of the tray-set green product and to formulate the managerial implications which can be applied by PT Garuda Indonesia.  The data collection was conducted in July – August 2012. Data was collected from 200 respondents who had used the services of PT Garuda Indonesia. Descriptive, Konjoint, and Structural Equation Modeling (SEM) was used to analyze the relationship between ATB, SN and PBC to the interest of using tray-set green product. The result of the study indicated that the attitude Toward Behavior, Subjective norms, perceive behavioral control had significant value to the interest. The attributive preferences desired from the tray-set green product are stronger materials, eco-friendly packaging and interesting shapes. The result of this study recommended that to improve the marketing mix strategies to enhance the passengers’ interest in using tray-set green product.